Synthesis and Characterization of Some New 3-(4-tert-Butylphenyl)-5-phenyl-4H-1,2,4-triazole Derivatives - Bekircan, Olcay (Asian Journal of Chemistry, 2010)
A series of new 3-(4-t-butylphenyl)-5-phenyl-4-(arylmethyleneamino)- 4H-1,2,4-triazole derivatives 3 were prepared in good yields by treatment of 4-amino-3-(t-butyl-phenyl)-5-phenyl-4H-1,2,4-triazole 2 with selected aldehydes. Compounds 3 were reduced with NaBH4 to afford the corresponding 3-(4-t-butylphenyl)-5-phenyl-4-(arylmethylamino)- 4H-1,2,4-triazole derivatives 4. Ten new compounds were synthesized and characterized by elemental analysis, 1H NMR, 13C NMR, IR and mass spectral data.